Pengembangan Buku Cerita Sembara untuk Mengembangkan Perilaku Prososial pada Anak Usia 5-6 Tahun - Husnah, Siti Lailatul; Reza, Muhammad; Setyowati, Sri; Ningrum, Mallevi Agustin (LP. Ma'arif Janggan Magetan, 2023)
This research is motivated by the development of children's prosocial behavior which is not yet in accordance with the standards for the developmental attainment level of children aged 5-6 years. Lack of prosocial behavior makes children less sensitive to their surroundings, such as children being unable to share, children being unable to help and children being unable to work together. The aim of this research is to determine the feasibility and effectiveness of using Sembara storybook media to develop prosocial behavior in children aged 5-6 years. This research uses a type of development research with the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The results of the effectiveness test using the Wilcoxon test show that 0.001 < 0.05, because the results of significance are less than 0.05, Ho is rejected and Ha is accepted. It can be concluded that the use of Sembara book media is effective in developing prosocial behavior in children aged 5-6 years.